Evaluating the readability, quality, and reliability of online information on sjogren's syndrome - Erkan Ozduran; Volkan Hanci (Indian Journal of Rheumatology)
Background: There are concerns over the reliability and comprehensibility of health-related information on Internet. The goal of our research was to analyze at the readability, reliability, and quality of information obtained from websites associated with Sjogren's syndrome (SS). Methods: In this cross-sectional study, the term “Sjogren's Syndrome” was used to perform a search on Google, and 75 eligible websites were identified on September 15, 2021. The Flesch Reading Ease Score (FRES), Flesch-Kincaid Grade Level, and Gunning Fog (GFOG) were used to evaluate the readability of the website. The Journal of American Medical Association (JAMA) score was used to assess the websites' reliability, the DISCERN score, the Health on the Net Foundation code of conduct (HONcode) was used to assess quality, and Alexa was used to analyze their popularity. Results: The results revealed that the mean FRES was 42.25 ± 17.11 (difficult), and the mean GFOG was 14.80 ± 3.56 years (very difficult). According to the JAMA scores, 24% of the websites had a high-reliability rating and 26.7% adhered to the HONcode. The readability was found to significantly differ from the reliability of the websites (P < 0.001). Moreover, websites with scientific content were found to have higher readability and reliability scores (P < 0.001). Conclusion: The readability of SS-related information on the Internet was found to be considerably higher than that recommended by the National Health Institute's Grade 6, with moderate reliability and fair quality. We believe that online information should have some level of readability and must have reliable content that is appropriate to educate the public, particularly for websites that provide with patient education material.